Poly (3-hydroxybutyrate-co-3-hydroxyvalerate)/fibrinogen/bredigite nanofibrous membranes and their integration with osteoblasts for guided bone regeneration - Monireh, Kouhi; Venugopal, Jayarama Reddy; Mohammadhossein, Fathi; Morteza, Shamanian; Afsaneh, Valipouri; Seeram, Ramakrishna (WILEY PERIODICALS, INC., 2019)
Guided bone regeneration (GBR) has been established to be an effective method for the repair of defective tissues, which is based on isolating bone defects with a barrier membrane for faster tissue reconstruction. The aim of the present study is to develop poly (hydroxybutyrate-co-3-hydroxyvalerate)(PHBV)/fibrinogen (FG)/bredigite (BR) membranes with applicability in GBR. BR nanoparticles were synthesized through a sol–gel method and characterized using transmission electron microscopy and X-ray diffractometer. PHBV, PHBV/FG, and PHBV/FG/BR membranes were fabricated using electrospinning and characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, contact angle, pore size, thermogravimetric analysis and tensile strength. The electrospun PHBV, PHBV/FG, and PHBV/FG/BR nanofibers were successfully obtained with the mean diameter ranging 240–410 nm. The results showed that Young’s modulus and ultimate strength of the PHBV membrane reduced upon blending with FG and increased by further incorporation of BR nanoparticles, Moreover hydrophilicity of the PHBV membrane improved on addition of FG and BR. The in vitro degradation assay demonstrated that incorporation of FG and BR into PHBV matrix increased its hydrolytic degradation. Cell-membrane interactions were studied by culturing human fetal osteoblast cells on the fabricated membrane. According to the obtained results, osteoblasts seeded on PHBV/FG/BR displayed higher cell adhesion and proliferation compared to PHBV and PHBV/FG membrane. Furthermore, alkaline phosphatase activity and alizarin red-s staining indicated enhanced osteogenic differentiation and mineralization of cells on PHBV/FG/BR membranes. The results demonstrated that developed electrospun PHBV/FG/BR nanofibrous mats have desired potential as a barrier membrane for guided bone tissue engineering.